Differences in physician and patient perceptions about insulin therapy for management of type 2 diabetes: the DAWN Japan study. (February 2014) - Yoshioka, Narihito; Ishii, Hitoshi; Tajima, Naoko; Iwamoto, Yasuhiko; ,
Abstract Objective: To better understand patient resistance to initiation of insulin therapy, this study examined the perception gap concerning initiation of insulin therapy between individuals with type 2 diabetes and their physicians by using data from the DAWN Japan study. Methods: The DAWN Japan study is a multi-center, questionnaire-based survey, conducted between 2004–2005. Patients recommended to start insulin therapy (n = 148) answered a questionnaire by rating degree of agreement with 16 statements concerning insulin therapy on a 5-point scale (1: strongly disagree to 5: strongly agree). Ratings of 1 and 2 were categorized as 'disagree' with a statement, and 3, 4, and 5 as 'agree'. Their attending physicians (n = 68) selected statements which could be associated with patient's concerns about insulin therapy. Results: Nearly all the patients agreed with the statements 'I don't want to inject myself for the rest of my life' (95%), and 'I don't want to be bothered with doing injections' (90%); fewer than half agreed with 'My friendships may suffer' (46%), and 'I don't understand why insulin is necessary for me' (45%). Estimation by the physicians and the actual perceptions patients reported differed significantly for 13 statements. Physicians seemed to particularly under-estimate the impact associated with social aspects of insulin use (e.g., 'I don't want to be different from others', 55% patients vs 7% physicians). On the contrary, the statement 'Injections are painful' was the only concern over-estimated by the physicians. Conclusions: It was demonstrated that differences in perceptions regarding insulin therapy exist between physicians and patients, particularly in terms of social impacts. The data, obtained in 2004, may not precisely reflect the present situation, but still represents a barrier to insulin therapy widely held by patients and physicians. These results suggest that appropriate understanding of patients' concerns about insulin therapy is important to encourage timely insulin initiation.